Family Life Experiences of Children After Divorce: A Qualitative Research Parental Alienation - Sümeyra Ceylan Dolanbay; Aslıhan Aykara (Sosyal Siyaset Konferansları Dergisi)
The family is the most natural and primary environment for the transformation of a child to an individual with healthy identity development and socialization. A divorced family is a type of family formed by death, divorce, and separation. The current study examines the alienation experiences of a child in a divorced family and the parents, especially the one who was unable to obtain custody after divorce, and the relevant processes. In this regard, the study discusses the experiences of adult individuals who underwent the process until the conclusion of the divorce case of their parents, which occurred before they reached the age of 18 years, and the resultant alienation from their parents. Experiences were revealed using structural family systems theory, which was developed through family interaction patterns. The study intends to recommend solutions to this issue. Toward this end, it conducts in-depth interviews with 29 subjects. The findings indicate that dysfunctional interaction patterns within the family witnessed prior to the before divorce period are related to the grounding of alienation experiences. The study observes that divorce and relevant issues are added to the process (before, during and after divorce) and strengthen alienation. The feelings and thoughts of the subjects toward their parents were formed by events experienced due to dysfunctional relationships within the family and the consequences of divorce. After the divorce, it has been observed that the alienation that the subjects experienced stemmed from their before divorce experiences. Based on the results, the study puts forward the most evident recommendations: To provide family counseling services specifically in the context of parental alienation throughout the stages of divorce and to popularize the practice of joint custody, which is an option in custody cases, for families deemed appropriate.